Factor VIIa Regulates the Expression of Caspase-3, MMP-9, and CD44 in SW620 Colon Cancer Cells Involving PAR2/MAPKs/NF-κB Signaling Pathways. (25th January 2013) - Wu, Ying; Zhang, Xianmei; Zhou, Hong; Chen, Dongdong; Xie, Hongxiang; Mu, Yuan; Wu, Biao; Yan, Jinchuan
<x xml:space="preserve">Abstract</x> Our previous study has demonstrated that TF/FVIIa and PAR2 are closely related to the proliferation and migration of colon cancer cell line SW620. However, the detailed molecular mechanisms in the process remain unclear. This study further investigated whether some important molecules (caspase-3, MMP-9 and CD44) are involved in the events. The results showed that PAR2-AP or FVIIa elicited time-dependent downregulation of caspase-3, and up-regulation of MMP-9 and CD44 in SW620 cells. The effects of FVIIa were TF-dependent and involving PAR2/MAPKs/NF-κB signal transduction pathways. Our study suggests that the links among PAR2/MAPKs/NF-κB may be blocked for effective treatments of colorectal cancers.